Predicting turnover intentions from leader-member exchange and team satisfaction in Singapore. - Koh, Jasmine Yi Ling. (2009)
Leader-member exchange (LMX) and team satisfaction are both potential sources of employee turnover that have been dealt with in entirely separate literatures. Since turnover is a costly and crucial issue in the business world today, in this study we will examine the relationships of the four dimensions of LMX (affect, contribution, loyalty and professional respect) and team satisfaction to employees’ intention to leave the organization.